Gender, Age, and Teaching Experience Factors in Creative Teaching Practices Among Islamic Education Lecturers - Asep - Kurniawan; Hakan Bayirli (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2024)
This study aims to evaluate creative teaching practices among Islamic Education lecturers at Muhammadiyah University of Cirebon and analyze the differences and relationships between these practices and demographic variables such as gender, age, and teaching experience. This research employs a quantitative approach with a survey method, using a five-point Likert scale questionnaire distributed online to 75 lecturers selected through simple random sampling. The instrument used consists of 24 items with high reliability (α = 0,941). Data analysis was conducted using IBM SPSS Statistics Version 28.0, including normality tests, descriptive analysis, and inferential analysis. The normality test results indicate that the data is normally distributed. Descriptive analysis shows that the lecturers' creative teaching practices are at a high level (mean = 3.99, SD = 0.471), with the item "Connecting issues with everyday life" having the highest average score (mean = 4.42, SD = 0.701). An independent t-test revealed no significant differences in creative teaching practices based on gender (t = -0.120, p = 0.905). Pearson correlation analysis also showed no significant relationship between gender, age, and teaching experience with creative teaching practices. These findings indicate that these demographic variables do not influence the level of creative teaching practices among Islamic Education lecturers. The implication is that creative teaching practices among Islamic education lecturers are consistently high, regardless of gender, age, or teaching experience, indicating the limited influence of these demographic factors.Keywords: Creative Teaching Practices, Islamic Education Lecturers, Descriptive Analysis, Inferential Analysis, Muhammadiyah University of Cirebon.